Factors Predicting Surgical Resection in Patients with Intrahepatic Cholangiocarcinoma and Cirrhosis. (1st August 2014) - Li, Hao; Wu, Jin-shu.; Wang, Xin-tian.; Lv, Pin; Gong, Lian-sheng; Liu, Gong; Tian, Bu-ning; Li, Ya-yong.; Jiang, Bo
ABSTRACT: Here, we investigate the potential factors that affect the outcome of patients with intrahepatic cholangiocarcinomas (ICC) and cirrhosis. We retrospectively reviewed the clinical data and pathological features of 58 patients with ICC and cirrhosis who underwent liver resection between July 2000 and March 2008, and analyzed the prognostic risk factors by means of univariate and multivariate analyses. The overall morbidity and mortality were 40% and 3.3%, respectively. The overall median survival was 24 months, and the 1-, 3-, and 5-year actuarial survival rates were 53%, 18%, and 10%, respectively. Univariate analysis showed that Child–Pugh classification, hypoalbuminemia, vascular invasion, lymphnodes metastasis, tumor-nodes-metastasis (TNM) staging system, positive surgical margins, and high perioperative blood transfusion volumes were all significantly associated with poor survival. Multivariate analysis confirmed that hypoalbuminemia, vascular invasion, positive surgical margins, and high perioperative blood transfusion volume were survival related, with hazard ratios (HR) of 2.58, 3.12, 3.57, and 1.98, respectively. Surgical resection is an effective treatment for patients affected by ICC and cirrhosis. Predictive factors, including hypoalbuminemia, vascular invasion, positive surgical margins, and high perioperative blood transfusion volumes are all related to poor survival.